Elaboração de um manual: proposta de aplicação de metodologias ativas de aprendizagem em curso superior de bacharel em nutrição - SILVA, Amanda Vitória Do Nascimento Da (2024)
One of the challenges of the current training of health professionals is the change from traditional teaching to a new method that allows the use of technological and strategic resources. In this sense, the present work aims to develop an instructional technology for teachers with proposals for active methodologies (MAPs) to assist in the teaching and learning process. This is a quantitative and qualitative methodological study that was carried out from February to June 2023, at the Faculty of Nutrition of the Federal University of Pará (UFPA) in Belém, focusing on the development of a manual-type instructional technology. The execution was divided into two stages: a) Situational diagnosis, with the characterization of the professors' profile through the application of an online questionnaire containing open and closed questions about socio-demographic data (age, gender), general academic training and use of active methodologies of learning; b) Elaboration of the Manual, based on the contents of the answers obtained with the teachers and bibliographic survey. The research was approved by the Research Ethics Committee of the Institute of Health Sciences at UFPA under number 5.872.241. Eleven professors participated in the research, of which four worked only in mandatory internships, so only seven met the study requirements. The sample, in its entirety, was composed of females with a mean age of 40 ± 7.4 years. It was observed that all participants (100.0%) had already had some contact and experience in applying MAP in the classroom, as well as considering that its use made the content more attractive to students. However, all indicated that they had some type of difficulty regarding its use in the classroom, the main ones reported being: lack of time for pre-class organization (71.4%) and for organization during class (57.1% ). The instructional technology developed was entitled: “Manual of Active Methodologies for Higher Education Teachers”, and was divided into eleven chapters, in which subjects related to MAPs in the classroom were presented, such as: team-based learning (ABE), team-based learning in problems (PBL), peer review, dramatization, case study, gamification, conceptual and mental map, podcast, problematization, flipped classroom and world café. The study made it possible to understand the difficulties related to the application of MAPs, and the need for training in the use of methodologies. In addition, it is expected that after the validation process, the prepared manual can encourage and assist professors in the application of MAPs in higher education.